Reserve Balancing in a Microgrid System for Safety Analysis⁎The first author would like to acknowledge the financial support of the Chair TRUST of Grenoble INP for his research stay at the Univ. Grenoble Alpes, Grenoble INP, Institute of Engineering Univ. Grenoble Alpes., LCIS, F-26000 Valence. Issue 2 (2020) - Kiebler, Clemens; Prodan, Ionela; Petzke, Felix; Streif, Stefan
Abstract: This work presents a robust MPC (Model Predictive Control) approach for reserve balancing in DC microgrid systems under uncertainties like wind power and energy price variations and different types of fault events. The robust MPC algorithm considers a variable-length prediction horizon which accounts for forecasts in energy price and renewable power over one day. Furthermore, a storage system is used to increase the utility of the demands and minimize the energy costs. The algorithm is tested for multiple fault types which affect the system (line and loss of power faults).